Employee Productivity Optimization: The Role of Communication, Facilities, and NWOW - Yohannes Sarwo Edi; Muhammad Yunus Amar (Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to analyze the influence of communication skills and work facilities on employee productivity at PT. Bank Negara Indonesia (BNI) Makassar, with New Ways of Working (NWOW) as a moderation variable. The quantitative method was used by involving 36 employees of the credit division as respondents. Data were collected through structured questionnaires and analyzed using multiple regression to evaluate direct influence as well as interactions to assess the effects of NWOW moderation. The results of the study show that communication skills and work facilities have a positive influence on employee productivity. However, the role of NWOW moderation was insignificant, suggesting that other factors such as time management and leadership may play a more dominant role. This research provides insight into HRM practices in PT. Bank Negara Indonesia Makassar, especially in the context of implementing flexible work.